2021
DOI: 10.3390/su131910620
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Satisfaction, Willingness to Revisit and Recommend, and Mountain Kangyang Tourism Spots Sustainability: A Structural Equation Modelling Approach

Abstract: The rapid development of society and economy has imposed insurmountable pressure on the urban population, and many people suffer from sub-health conditions. Kangyang tourism (KT), which combines the concepts of health preservation, ecological resources, and tourism activities, has developed rapidly in China since the concept was first introduced. Although previous studies have examined the relationship among experience, satisfaction, and intention, there is a lack of study of experience value’s impact on Mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 77 publications
3
36
1
1
Order By: Relevance
“…Among the more than 200 national-level scenic spots in China, more than 90% are located in mountainous areas. Zeng et al (2021) suggested that future studies concerning health and wellness tourism should focus on mountain-based opportunities because specific locations and traditional customs that are characterized by a particular microclimate may contribute to longevity and health according to Chinese culture [16]. Similar to rural tourism, mountain-based tourism has been impacted by low efficiency, overdevelopment, and homogeneous environments, which has, in turn, affected the competitiveness of mountain-based health and wellness tourism [17].…”
Section: Heath Tourism Emerging In Chinese Mountainous Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the more than 200 national-level scenic spots in China, more than 90% are located in mountainous areas. Zeng et al (2021) suggested that future studies concerning health and wellness tourism should focus on mountain-based opportunities because specific locations and traditional customs that are characterized by a particular microclimate may contribute to longevity and health according to Chinese culture [16]. Similar to rural tourism, mountain-based tourism has been impacted by low efficiency, overdevelopment, and homogeneous environments, which has, in turn, affected the competitiveness of mountain-based health and wellness tourism [17].…”
Section: Heath Tourism Emerging In Chinese Mountainous Areasmentioning
confidence: 99%
“…The measurement of customers' behavioral intentions, such as the likelihood of converting a one-time purchaser into a long-time customer or of a customer recommending their experience to others, and customer satisfaction has a long history in the fields of marketing, management, and tourism [40]. Regarding tourist destination research, satisfaction with travel destinations is directly linked to tourists' behavioral intentions [16]. Chang et al (2016) examined the satisfaction (e.g., overall satisfaction, satisfaction compared to travelers' own time and efforts, and satisfaction compared to other ports of call) of cruise travelers using a sample population's pre-visit expectations and post-visit experiences, demonstrating the impact of overall satisfaction on the likelihood of revisiting and recommending the visit to others [41].…”
Section: Theoretical Framework 221 Satisfaction-behavioral Intentionsmentioning
confidence: 99%
“…We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021). We also noted that three studies were conducted in the USA context (Chua et al, 2020(Chua et al, , 2021Milman et al, 2020;Rasoolimanesh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, socio-demographic variables (Gender, marital status, education and monthly income), functional value, contextual value, emotional value, cognitive value, economic value, are more significant drivers of tourist post-COVID-19 travel intention. Past studies found that the above-mentioned factors are a positive effect on post-COVID-19 travel intention towards the destination (Rasoolimanesh et al, 2021;Sinha and Nair, 2021;Zeng and Li, 2021). However, some previous studies found that perceived positive impact of COVID-19, positive emotion, emotional attachment, brand humanization, shared emotions, perceived response efforts, physical factors, socio-psychological factors, financial factors, physical, socio-psychological and financial drivers have a direct and positive effect on tourist travel intention (Agyeiwaah et al, 2021;Ahmad et al, 2020bAhmad et al, , 2021aChua et al, 2021;Hang et al, 2020).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Based on the American Customer Satisfaction Index, this paper takes AMOS (Analysis of Moment Structure) and SPSS statistical software as examples to test the validity and practicability of the TSRTD (Tourist Satisfaction of Rural Tourism Destination) model [5]. The article proposes a framework of "experience value (functional value, situational value, emotional value, cognitive value, economic value), satisfaction and post-travel revisit and recommendation willingness" to investigate Kangyang Mountain tourism [6]. This paper proposes a tourist satisfaction model of a destination and takes Guilin as a case to study the causes and consequences of tourist satisfaction [7].…”
Section: Introductionmentioning
confidence: 99%